Analisis Produksi Dan Pemasaran Kakao Di Gampong Tunong Kecamatan Keumala Kabupaten Pidie - Ibrahim Ali (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. The agricultural sector is a sector that is able to survive in conditions of economic crisis hit Indonesia. This sector plays an important role in the economic recovery in Indonesia, and also became one of the main components of the program and the government's strategy to alleviate kemiskinan.Tujuan Research: To determine Are land, capital and labor influence on produksi.Untuk know cocoa marketing system in the Gampong Tunong Keumala Pidie District. This research purposed survey method. Furthermore, to determine the sample farmers used the technique